A Useful Gadget to Reduce the Radiation Dose of Interventionist's Hands. Issue 5 (May 2017) - Zeinali-Rafsanjani, Banafsheh; Rasekhi, Alireza; Saeedi-Moghadam, Mahdi; Zarei, Fariba; Jalli, Reza; Sefidbakht, Sepideh; Pishdad, Parisa
Abstract : Abstract: Increased demand for interventional radiology techniques has interventionists performing a large number of these procedures. Measurements and calculations have shown that the radiation doses received by these specialists can exceed the threshold of radiation-induced deterministic effects unless radiation protection procedures and devices are used. Proper usage of radiation protection devices can protect them from radiation-induced effects, even with a high workload. Occupational radiation protection entails proper training of interventionists to increase their awareness about available appropriate protection tools and equipment, and devices that can be used to minimize exposure, such as needle holders, tubing extensions, and injectors. This study introduces a device that can be used to fix the catheter to prevent the physician from holding the catheter by hand. The authors, also, discuss the importance of radiation protection training along with the training on new medical equipment, which can be applied to reduce the radiation dose.